Bioactivity Determination of Native and Variant Forms of Therapeutic Interferons. (17th February 2011) - Larocque, Louise; Bliu, Alex; Xu, Ranran; Diress, Abebaw; Wang, Junzhi; Lin, Rongtuan; He, Runtao; Girard, Michel; Li, Xuguang
Abstract : The traditional antiviral assays for the determination of interferon potency are reported to have considerable variability between and within assays. Although several reporter gene assays based on interferon-inducible promoter activities have been reported, data from comprehensive validation studies are lacking and few studies have been conducted to analyze the variant forms of interferons, which could have undesirable clinical implications. Here, a reporter gene assay employing a HEK293 cell line stably transfected with luciferase gene under the control of interferon-stimulated response element promoter was developed and validated. The assay was found to be more sensitive, with a larger detection range than the antiviral assay. Several cytokines tested did not interfere with the test, suggesting the assay possesses a certain degree of selectivity. Moreover, the robustness of the assay was demonstrated by minimal variations in the results generated by different analysts and cell passage number (up to 52 passages). Finally, the method was employed to analyze several interferon variants (interferon-α 2a) and we found that the aggregated form has completely lost its potency; while a modest loss of bioactivity in oxidized interferon was observed (approx. 23%), the deamidated form essentially retained its activity.